ToxicoDB: an integrated database to mine and visualize large-scale toxicogenomic datasets. Issue Volume 48:Issue W1(2020) (18th May 2020) - Nair, Sisira Kadambat; Eeles, Christopher; Ho, Chantal; Beri, Gangesh; Yoo, Esther; Tkachuk, Denis; Tang, Amy; Nijrabi, Parwaiz; Smirnov, Petr; Seo, Heewon; Jennen, Danyel; Haibe-Kains, Benjamin
Abstract: In the past few decades, major initiatives have been launched around the world to address chemical safety testing. These efforts aim to innovate and improve the efficacy of existing methods with the long-term goal of developing new risk assessment paradigms. The transcriptomic and toxicological profiling of mammalian cells has resulted in the creation of multiple toxicogenomic datasets and corresponding tools for analysis. To enable easy access and analysis of these valuable toxicogenomic data, we have developed ToxicoDB (toxicodb.ca ), a free and open cloud-based platform integrating data from large in vitro toxicogenomic studies, including gene expression profiles of primary human and rat hepatocytes treated with 231 potential toxicants. To efficiently mine these complex toxicogenomic data, ToxicoDB provides users with harmonized chemical annotations, time- and dose-dependent plots of compounds across datasets, as well as the toxicity-related pathway analysis. The data in ToxicoDB have been generated using our open-source R package, ToxicoGx (github.com/bhklab/ToxicoGx ). Altogether, ToxicoDB provides a streamlined process for mining highly organized, curated, and accessible toxicogenomic data that can be ultimately applied to preclinical toxicity studies and further our understanding of adverse outcomes.